Commodity Markets Outlook, April 2019 - World Bank Group (World Bank, Washington, DC, 2019)
Commodity Markets Outlook provides market analysis for major commodity groups -- energy, metals, agriculture, precious metals, and fertilizers. The report forecasts prices for 46 key commodities, including oil. It is published in April and October. The April 2019 report has a special focus on food prices.